SYNAPTONEMAL COMPLEX-ANALYSIS IN SPERMATOCYTES OF TILAPIA, OREOCHROMIS-NILOTICUS (PISCES, CICHLIDAE) - Foresti, F.; Oliveira, C.; Galetti, P. M.; Dealmeidatoledo, L. F. (Natl Research Council Canada, 1993)
Some adaptations of the synaptonemal complex (SC) whole-mounting technique first used in plants permitted its application to meiotic studies in tilapia, Oreochromis niloticus. Direct observation of the chromosome pairing process and bivalent structure during the meiotic prophase of this fish species by light and electron microscopy permitted the analysis of SCs in autosomes and the possible identification of sex chromosomes. The analysis of SCs in spermatocytes of 0. niloticus revealed that all 22 bivalent chromosomes completely paired, except for the occurrence of a size heteromorphism in the terminal region of the largest bivalent associated with the presence of an incompletely paired segment during the synapsis process, which may be the cytological visualization of an XX/XY sex chromosome system in this species.
Keywords: FISH CYTOGENETICS; SYNAPTONEMAL COMPLEX; FISH MEIOSIS; SEX CHROMOSOMES; NUCLEOLUS ORGANIZER REGIONS